2020
DOI: 10.3390/su12114620
|View full text |Cite
|
Sign up to set email alerts
|

Historic Building Energy Audit and Retrofit Simulation with Hemp-Lime Plaster—A Case Study

Abstract: Hemp-lime composite is a natural material, which is being increasingly used and studied in the construction sector, thanks to its recyclability, hygrothermal comfort and healthiness features. The aim of this paper is to test the benefits in terms of energy efficiency achieved through the use of hemp-lime composite as insulation in a possible refurbishment intervention. With the aim of extending the knowledge about the benefits achieved through from the integration of this natural material into construction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Some papers discuss the energetic performance of historic buildings after the application of hemp-lime compared with gypsum lime [61]. For instance, Agliata et al [62], using a case study "Palazzo Jadicicco", found that the overall energy performance of the building increased by around 20% with a one-level improvement of the building energy class, from E to D. Besides, if it is a good result, it should underline that the decrease in thermal transmittance was not sufficient to fulfill the regulatory requirements, in Italy.…”
Section: State-of-artmentioning
confidence: 99%
“…Some papers discuss the energetic performance of historic buildings after the application of hemp-lime compared with gypsum lime [61]. For instance, Agliata et al [62], using a case study "Palazzo Jadicicco", found that the overall energy performance of the building increased by around 20% with a one-level improvement of the building energy class, from E to D. Besides, if it is a good result, it should underline that the decrease in thermal transmittance was not sufficient to fulfill the regulatory requirements, in Italy.…”
Section: State-of-artmentioning
confidence: 99%
“…Despite the abundance of the literature on sustainability and enormous advocation for the use of such sustainable materials as better alternatives for reducing the adverse effects caused by the production and use of conventional materials in Ghana (Agyekum et al, 2020), there is a lack of studies about the potential use of hemp as a sustainable building material. Though the value of hemp has been questioned and relegated to the background in Ghana over the years, evidence from the body of knowledge worldwide suggests that it is an essential material in the building industry following the numerous properties it possesses (Kolodinsky et al, 2020;S aez-P erez et al, 2020;Agliata et al, 2020). As a matter of fact, following the deliberations on the possible passage of a legal bill in Ghana for the cultivation of industrial and medicinal hemp, it is crucial to seize this opportunity to explore this useful material as an alternative material in the delivery of green buildings which is gaining attention in Ghana.…”
Section: Factors Limiting the Adoption Of Hempmentioning
confidence: 99%
“…S aez-P erez et al (2020) identified this problem and advised that to ensure that countries move into mainstream production and use of hemp in building products, green building designers must understand these innovative materials and encourage its adoption for buildings. Literature summarises the factors limiting the adoption of hemp-based building materials to include technical, commercial, knowledge, regulatory, psychological and invisible issues (Agliata et al, 2020;Ronchetti, 2007). Table 2 summarises most of these factors as extracted from the literature 3.…”
Section: Hemp As An Alternative Sustainable Building Materials and Ba...mentioning
confidence: 99%
“…LCA can be a useful tool for the conservation of historic buildings [31][32][33]. LCA can contribute to the reduction in LCCO 2 emissions of historic buildings by prolonging the service lives of used materials [34], proposing energy-efficient seismic strengthening [35] and improving the energy efficiency of buildings [36][37][38][39]. However, the reliable application of LCA to conservation practice requires further investigation and practice [40][41][42].…”
Section: Introductionmentioning
confidence: 99%